Rancang Bangun Sistem Database Tilang Kendaraan Angkutan Umum dan Angkutan Barang Dinas Perhubungan Kota Jayapura - Fifian Theresia Sibi; Jim Lahallo (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
The Jayapura City Transportation Agency faces significant challenges in managing traffic violation data due to rapid population and economic growth. The use of Excel-based systems has proven inadequate, so a more integrated and efficient information system update is needed. Thus, the research and development method to design a web-based data archiving information system application with a waterfall methodology approach. It is hoped that this application can improve the efficiency of filing and searching for violation data, as well as support better traffic control in Jayapura City.